Osteopontin Expression in Human and Murine Obesity: Extensive Local Up-Regulation in Adipose Tissue but Minimal Systemic Alterations - Kiefer, Florian W.; Zeyda, Maximilian; Todoric, Jelena; Huber, Joakim; Geyeregger, René; Weichhart, Thomas; Aszmann, Oskar; Ludvik, Bernhard; Silberhumer, Gerd R.; Prager, Gerhard; Stulnig, Thomas M. (Endocrinology (Philadelphia), 2008)
Obesity is associated with a chronic low-grade inflammation characterized by macrophage infiltration of adipose tissue (AT) that may underlie the development of insulin resistance and type 2 diabetes. Osteopontin (OPN) is a multifunctional protein involved in various inflammatory processes, cell migration, and tissue remodeling. Because these processes occur in the AT of obese patients, we studied in detail the regulation of OPN expression in human and murine obesity. The study included 20 morbidly obese patients and 20 age- and sex-matched control subjects, as well as two models (diet-induced and genetic) of murine obesity. In high-fat diet-induced and genetically obese mice, OPN expression was drastically up-regulated in AT (40 and 80-fold, respectively) but remained largely unaltered in liver (<2-fold). Moreover, OPN plasma concentrations remained unchanged in both murine models of obesity, suggesting a particular local but not systemic importance for OPN. OPN expression was strongly elevated also in the AT of obese patients compared with lean subjects in both omental and sc AT. In addition, we detected three OPN isoforms to be expressed in human AT and, strikingly, an obesity induced alteration of the OPN isoform expression pattern. Analysis of AT cellular fractions revealed that OPN is exceptionally highly expressed in AT macrophages in humans and mice. Moreover, OPN expression in AT macrophages was strongly up-regulated by obesity. In conclusion, our data point toward a specific local role of OPN in obese AT. Therefore, OPN could be a critical regulator in obesity induced AT inflammation and insulin resistance.